PDMS-based dual-channel pneumatic micro-actuator - Rehman, Tariq; Nafea, Marwan; Faudzi, Ahmad Athif; Saleh, Tanveer; Mohamed Ali, Mohamed Sultan (IOP Publishing, 2019)
This paper presents a monolithic novel polydimethylsiloxane-based dual-channel bellows-structured pneumatic actuator, fabricated through a sacrificial molding technique. A finite element analysis was performed to find the optimal structure and analyze the bending performance of the square-bellows actuator. The actuator was designed with an overall cross-sectional area of 5 × 5 mm2, while its structural parameters were characterized in terms of 8, 12, 16 and 20 number of bellows. The actuator models were fabricated using acrylonitrile butadiene styrene-based sacrificial molds to form the channel and bellows structures. The experimental validation has revealed that the actuator having highest number of bellows with a size of 5 × 5 × 68.4 mm3 attained a smooth bi-directional bending motion, with maximum angles of −65° and 75°, and force of 0.166 and 0.221 N under left and right channel actuation, respectively, at 100 kPa pressure. Hence, the state-of-the-art dual-channel square-bellows actuator was able to achieve an optimal bi-directional bending with slight variations to change in temperature, which would push the boundaries of soft robotics toward the development of safer and more flexible robotic surgical tools.